Membranous Tonsilitis as a Clinical Presentation of Acute Monocytic Leukemia: A Rare Case Report - Linggawan, Stephani; Wibowo, Eric Satrio Adi; Gunawan, Catherine Keiko; Raharjo, Budiono; Sumarpo, Anton; Raharjo, Yohanes Timothy; Dwijayanti, Ni Made Intan; Yudho Bintoro, Siprianus Ugroseno (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Acute myeloid leukemia (AML) is a heterogeneous hematologic malignancy characterized by the clonal proliferation of immature myeloid precursor cells in the bone marrow and peripheral circulation. Hematologic manifestations such as anemia, thrombocytopenia, and leukocytosis are welldocumented, its association with oral involvement, particularly tonsillitis, is a rare presenting feature. Objective: This case report emphasizes membranous tonsilitis as the primary presenting feature in acute monocytic leukemia (AML-M5). The aim of writing this case study is to provide an illustration that the causes of membranous tonsillitis, beside from the infection, can also be caused by infiltration of leukemia cells. Case Presentation: We report a case of a 27-year-old female presented with fever and was found to have a fluctuating mass on the right side of the neck along with gingival swelling and hyperemic, hypertrophic tonsils with a membranous exudate. The diagnosis from bone marrow aspiration and immunophenotyping revealed as acute monocytic leukemia (AML-M5). Bacterial and fungal infections were excluded through gram staining, potassium hydroxide (KOH) examination, and throat swab culture. The patient was initially stabilized with hydroxyurea, with subsequent clinical improvement, before being referred to a tertiary center for definitive management. Result: This diagnostic workup altogether from all the clinicians leads to the diagnosis of acute myeloid leukemia (AML-M5). Conclusion: This case highlights primary tonsilitis as the primary presenting feature of acute myeloid leukemia (AML-M5), emphasizing the need for continued monitoring and regular follow-up assessment to detect potential relapses and ensure optimal disease management